Solomon Islands : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report, 2022)
Strong and timely containment measures have successfully prevented a domestic COVID-19 outbreak but have also weighed on economic activity and aggravated pre-existing socio-economic tensions. Following a contraction in 2020, growth is projected to recover gradually starting this year and to gain strength as containment measures are relaxed and borders re-opened. Elevated pandemic-related uncertainties as well as longstanding social, economic and governance challenges and vulnerability to natural disasters pose headwinds to inclusive growth. Despite strong external buffers, weaker fiscal position increases vulnerability to shocks, while the decline in logging weighs on fiscal revenues and growth prospects.